A method for removing alkali from garnet-type solid electrolyte
By using a combination of organic solvents and alkaline removers in garnet-type solid electrolytes, the problem of increased alkalinity on the surface is solved, the alkali content is effectively reduced and the performance is maintained, while improving the safety of the alkaline removal process. safety and environmental protection.
Patent Information
- Application Number
- CN202411194937.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-08-29
AI Technical Summary
The solid electrolyte of garnet type reacts with the water and carbon dioxide in the air, forming low-activated lithium carbonate and lithium hydroxide, resulting in a significant increase in surface alkalinity, affecting its performance, hindering its commercial application and large-scale production. .
The alkaline method of a garnet -type solid electrolyte, including testing the alkali content of its surface, dispersed it into an organic solvent, and adds alkaline deepening agent according to the alkaline content for dispersing treatment. The alkaline agent includes ethyleine tetrazide, trifluoroethane, amino sulfonic acid, etc.
It effectively reduces the alkali content of the garnet-type solid electrolyte to 0.05% without damaging its structure. The alkali removal process is safe and environmentally friendly, avoiding the generation of waste liquid and reducing the cost of alkali removal.
Smart Images

Figure CN118702147B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid electrolyte preparation, and in particular relates to a method for removing alkali from a garnet-type solid electrolyte. Background Art
[0002] Garnet-type solid electrolyte Li 6.5 LqCy 1.5 Ta 0.5 O 12 (LLZTO) has high lithium ion conductivity (>10 - 3 S cm -2 ), wide electrochemical range (>6V) and stability to metal anodes have attracted wide attention. At the same time, LLZTO has been widely used in the field of lithium-ion batteries as a coating agent for positive / negative electrode materials, an active filler for organic-inorganic composite solid electrolytes, and a coating material for ceramic diaphragms.
[0003] The lithium-rich phase on the surface of LLZTO will react with moisture and carbon dioxide in the air to form a large amount of low-activity substances such as lithium carbonate and lithium hydroxide on the surface, which greatly increases the alkalinity of the surface and thus greatly reduces its performance, which seriously hinders the commercial application and large-scale production of LLZTO. Therefore, the surface needs to be chemically treated before use.
[0004] Chinese patent document CN118136930A (202211489403.8) discloses a method for surface treatment of lithium lanthanum zirconium oxide solid electrolyte and its application. The patent uses inorganic dilute acid to treat the surface of solid electrolyte to generate lithium hydroxide and lithium carbonate. However, the use of inorganic acid treatment will destroy the structure of lithium lanthanum zirconium oxide solid electrolyte, reduce its lithium ion conductivity, and seriously reduce its performance. Chinese patent document CN112290082A (202011173688.5) discloses a surface treatment method of garnet-type solid electrolyte, which first removes impurities generated on the surface of garnet electrolyte by pre-treating garnet electrolyte powder material. One of the pretreatment methods is to treat the garnet electrolyte powder material with acid, and the acid solution is any one of nitric acid, sulfuric acid, hydrochloric acid, acetic acid or organic acid. The inorganic acid used in this patent is mostly a strong acid with strong corrosiveness, which is difficult to operate and extremely dangerous during use. At the same time, the use of highly corrosive inorganic acid will cause a large amount of waste liquid to be generated, which is not environmentally friendly and will cause huge alkali removal costs. The organic acid used is one of acetic acid, citric acid and tartaric acid. The degree of ionization of these acids is relatively low, and it is difficult to effectively remove lithium carbonate and lithium hydroxide. In addition, when these acids are mixed with garnet electrolyte powder to remove alkali, it is difficult to remove excess acid, thereby introducing a large amount of impurities, causing the performance of garnet electrolyte powder to decrease. Summary of the invention
[0005] The invention provides a method for removing alkali from a garnet-type solid electrolyte in order to solve the problems existing in the prior art, such as poor air stability of the solid electrolyte, low lithium ion conductivity caused by lithium carbonate and lithium hydroxide generated on the surface, and the like.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for dealkali treatment of a garnet-type solid electrolyte (LLZTO), comprising the following steps:
[0008] (1) Testing the alkali content on the surface of garnet-type solid electrolyte;
[0009] (2) dispersing the garnet-type solid electrolyte in an organic solvent to obtain a garnet-type solid electrolyte dispersion;
[0010] (3) Calculating the mass of the alkali contained in the garnet-type solid electrolyte according to the alkali content obtained in step (1), adding a de-alkali agent to the dispersion of step (2) according to the mass of the alkali, and performing a dispersion treatment, followed by filtering and drying; the de-alkali agent comprises at least one of ethylenediaminetetraacetic acid, trifluoroacetic acid, aminosulfonic acid, hydroxyethylidene diphosphonic acid, aminotrimethylphosphinic acid, ethylenediaminetetramethylphosphinic acid, methanesulfonic acid, tetraethylammonium perfluorooctanesulfonate, aniline sulfate, and methyl trifluoromethanesulfonate;
[0011] (4) The alkali content in the garnet-type solid electrolyte was tested again.
[0012] Preferably, the above steps (1) to (4) are repeated to further reduce the alkali content of LLZTO.
[0013] Preferably, the alkali content on the surface of the garnet-type solid electrolyte in step (1) includes OH - Mass content and CO3 2- quality content.
[0014] The alkali content test adopts the common method in this field. - The content and CO3 2- The calculation method of the content is:
[0015] W(OH - )=(2V1-V2)x0.001C HCI x17x100% / m;
[0016] W(CO3 2- )=(V2-V1)x0.001C HCI x60x100% / m;
[0017] in:
[0018] W(OH - ) is the OH in the solid electrolyte material - Content;
[0019] W(CO3 2- ) is CO3 in the solid electrolyte material 2- Content;
[0020] V1 is the volume of hydrochloric acid consumed in the first identification, in ml;
[0021] V2 is the volume of hydrochloric acid consumed in the second identification, in ml;
[0022] C HCI is the solubility of hydrochloric acid solution, in mol / L;
[0023] m is the mass of the solid electrolyte material powder to be tested, in g.
[0024] The product of the alkali content in step (1) and the mass of the sample to be treated is the mass of the alkali contained.
[0025] Preferably, in step (2), the mass ratio of LLZTO to the volume ratio of the organic solvent is 1 g: 5-100 mL, g / mL, preferably 1 g: 20-50 mL.
[0026] Preferably, the organic solvent in step (2) is at least one of acetonitrile, ethanol, tetrahydrofuran, carbon disulfide, acetone, N,N-dimethylamide, N,N-dimethylthiourea, melamine, propylene glycol, sorbitol, hydrazine hydrate, dimethyl sulfoxide, DMAC, dimethylformamide, acetone, ether, toluene, chloroform, carbon tetrachloride, cyclohexane, petroleum ether, dichloromethane, and ethyl acetate. More preferably, it is one of ethanol, tetrahydrofuran, and carbon disulfide.
[0027] Preferably, the mass ratio of the alkali to the alkali-removing agent in step (3) is 1:1-125, preferably 1:10-50.
[0028] Preferably, the alkali remover in step (3) comprises at least one of ethylenediaminetetraacetic acid, trifluoroacetic acid, aminosulfonic acid (NH2SO3H), hydroxyethylidene diphosphonic acid (HEDP), aminotrimethylphosphinic acid (ATMP), ethylenediaminetetramethylphosphinic acid (EDTMP), ammonium methanesulfonate, tetraethylammonium perfluorooctanesulfonate, aniline sulfate (C6H9NO4S), and methyl trifluoromethanesulfonate.
[0029] Further preferably, the de-alkali agent in step (3) is trifluoroacetic acid, tetraethylammonium perfluorooctane sulfonate, or ethylenediaminetetraacetic acid.
[0030] Preferably, the dispersion treatment in step (3) includes stirring dispersion and ultrasonic dispersion.
[0031] Preferably, the dispersion treatment time in step (3) is 0.1 to 30 h, preferably 0.25 to 18 h.
[0032] Preferably, the drying in step (3) includes at least one of vacuum drying, nitrogen drying, and argon drying.
[0033] Preferably, the drying temperature in step (3) is 30-500° C., preferably 100-400° C. The drying time is 1-48 hours, preferably 4-24 hours.
[0034] Beneficial effects of the present invention:
[0035] The present invention can effectively remove the alkali on the surface of the garnet-type solid electrolyte, reducing the alkali content to 0.05% without any effect on the structure of the solid electrolyte. In addition, the dealkali method of the present invention is safe and simple, and the solvent used in the dealkali process can be reused without generating any waste liquid, which greatly improves the safety of the dealkali process, and is extremely safe, environmentally friendly and low-cost.
[0036] The present invention tests the alkali content before removing the alkali, and determines the mass of the added acid according to the alkali content, which can effectively remove the alkali on the surface of the solid electrolyte and avoid the corrosion of the solid electrolyte by excessive acid. Secondly, it can also avoid the waste caused by excessive acid, and avoid the corrosion of instruments and equipment by acid and the generation of waste liquid.
[0037] The dealkali method of the present invention does not use water, which effectively avoids water damage to the solid electrolyte. After the garnet solid electrolyte is treated with water, a large amount of lithium carbonate and lithium hydroxide are produced on its surface. The XRD spectrum at this time shows that a large amount of impurities are produced in its crystals, which has a great impact on the performance of the solid electrolyte. At this time, the lithium ion conductivity is increased from the initial 9.0x10 -4 S cm -1 Down to 1.1x10 -4 S cm -1 However, after using an organic solvent to remove the alkali on the surface of the solid electrolyte, its XRD did not change and its lithium ion conductivity remained very high.
[0038] At the same time, the treatment by the method of the present invention can effectively inhibit the re-generation of surface alkali. After the alkali is removed, it is placed in the air for 15 days and tested again by XRD. No impurity phase is detected on the surface, and its lithium ion conductivity remains high. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1This is the XRD pattern of the newly prepared garnet-type solid electrolyte.
[0040] Figure 2 This is the XRD spectrum of the garnet-type solid electrolyte after the surface alkali removal treatment in Example 1.
[0041] Figure 3 This is the XRD spectrum of the garnet-type solid electrolyte after the surface alkali removal treatment in Example 2.
[0042] Figure 4 This is the XRD spectrum of the garnet-type solid electrolyte after the surface alkali removal treatment in Example 3.
[0043] Figure 5 This is the XRD spectrum of the garnet-type solid electrolyte after the surface alkali removal treatment in Example 4.
[0044] Figure 6 This is the XRD spectrum of the garnet-type solid electrolyte after the surface alkali removal treatment in Example 4 after being placed for 15 days.
[0045] Figure 7 This is the XRD spectrum of the garnet-type solid electrolyte after surface alkali removal treatment in Comparative Example 1.
[0046] Figure 8 This is the XRD spectrum of the garnet-type solid electrolyte after surface alkali removal treatment in Comparative Example 2.
[0047] Fig. 9 This is the XRD spectrum of the garnet-type solid electrolyte after surface alkali removal treatment in Comparative Example 3. DETAILED DESCRIPTION
[0048] The technical scheme of the present invention is further described in detail below in conjunction with specific examples. The raw materials used in the examples and comparative examples of the present invention are all common commercially available products.
[0049] The newly prepared garnet-type solid electrolyte was tested by XRD, and its crystal structure was a pure cubic phase, and no other impurities were detected. This is because the alkali content of the newly prepared solid electrolyte is very low, and it can be assumed to be alkali-free. Figure 1 It was pressed into a disc for impedance testing, and its lithium ion conductivity was 9.0x10 -4 S cm -1 .
[0050] Example 1
[0051] A method for removing alkali from a garnet-type solid electrolyte (LLZTO) comprises the following steps:
[0052] Weigh 10g of LLZTO, test its alkalinity content to be 3%, and calculate the alkalinity content to be 0.3g. Add 10g of LLZTO powder to 200mL of ethanol, then add 3g of trifluoroacetic acid to neutralize and remove the alkali, stir for 18h, filter, and dry at 400℃ in vacuum for 4h to obtain the LLZTO after alkalinity removal. Test again and its alkalinity content is 0.7%. XRD of the LLZTO after alkalinity removal shows that it is a pure phase. Due to the low alkali content, no impurities are detected (such as Figure 2 ). According to the impedance test method of LLZTO before de-alkali, the lithium ion conductivity of LLZTO after de-alkali is 8.8x10 -4 S cm -1 After being placed in the air for 15 minutes, the alkali content was tested again and found to be 0.78%.
[0053] Example 2
[0054] A method for removing alkali from a garnet-type solid electrolyte (LLZTO) comprises the following steps:
[0055] Weigh 15g of LLZTO, test its alkalinity content to be 2.4%, and calculate the alkalinity content to be 0.36g. Add 15g of LLZTO powder to 500mL of carbon disulfide, then add 18g of tetraethylammonium perfluorooctanesulfonate to neutralize and remove the alkali, and stir for 10h, then filter, and dry at 300℃ in a nitrogen atmosphere for 5h to obtain the LLZTO after dealkali, and test its alkalinity content again to be 0.5%. The XRD of the LLZTO after dealkali shows that it is a pure phase. Due to the low alkali content, no impurities were detected (such as Figure 3 ). Its lithium ion conductivity is 8.9x10 -4 S cm -1 After being placed in the air for 15 minutes, the alkali content was tested again and found to be 0.52%.
[0056] Example 3
[0057] A method for removing alkali from a garnet-type solid electrolyte (LLZTO) comprises the following steps:
[0058] Weigh 5g of LLZTO, test its alkalinity content to be 2.2%, and calculate the alkalinity content to be 0.11g. Add 5g of LLZTO powder to 250mL of tetrahydrofuran, then add 5.5g of ethylenediaminetetraacetic acid to neutralize and remove the alkali, and ultrasonically disperse for 15 minutes, then filter, and then dry at 100°C in an argon atmosphere for 24h to obtain the LLZTO after dealkali, and test its alkalinity content again to be 0.17%. The XRD of the LLZTO after dealkali shows that it is a pure phase. Due to the low alkali content, no impurities were detected (such as Figure 4 ). Its lithium ion conductivity is 8.5x10 -4 S cm-1 After being placed in air for 15 minutes, the alkali content was tested again and found to be 0.21%.
[0059] Example 4
[0060] The LLZTO sample after de-alkali in Example 3 was de-alkalied three times again, and the alkali content was tested again to be 0.05%. The XRD of the de-alkali LLZTO showed that it was a pure phase. Due to the low alkali content, no impurities were detected (such as Figure 5 ). Its lithium ion conductivity is 8.3x10 -4 S cm -1 After the solid electrolyte after alkali removal in Example 4 was placed in the air for 15 days, the alkali content on its surface was tested again, and the alkali content was 0.08%. The XRD pattern was tested to be pure phase, and no impurities were detected (such as Figure 6 ). Its lithium ion conductivity is 8.0x10 -4 S cm -1 .
[0061] Comparative Example 1
[0062] A method for removing alkali from a garnet-type solid electrolyte (LLZTO) comprises the following steps:
[0063] Weigh 20g of LLZTO and test its alkalinity content to be 2.7%, and calculate the alkalinity content to be 0.54g. Add 20g of LLZTO powder to 200mL of water, then add 7g of hydrochloric acid to neutralize and remove the alkali, and ultrasonically disperse for 10 minutes. Then filter to obtain the acid-treated LLZTO, and then dry it at 100°C in an argon atmosphere for 24h to obtain the de-alkali LLZTO, and test its alkalinity content again to be 1.5%. The XRD of the de-alkali LLZTO shows the presence of Li2ZrO3 impurity phase (such as Figure 7 ), its lithium ion conductivity is 3.2x10 -4 S cm -1 .
[0064] Comparative Example 2
[0065] Weigh 5g of LLZTO and test its alkalinity content to be 3.2%, and calculate the alkalinity content to be 0.16g. Add 5g of LLZTO powder to 300mL of tetrahydrofuran, then add 4.5g of tartaric acid to neutralize and remove the alkali, and ultrasonically disperse for 30 minutes. Then filter to obtain the acid-treated LLZTO, and then dry it at 120°C in an argon atmosphere for 24h to obtain the de-alkali LLZTO, and test its alkalinity content again to be 2.1%. The XRD pattern of the de-alkali LLZTO shows the presence of Li2ZrO3 impurity phase (such as Figure 8 ), its lithium ion conductivity is 4.8x10 -4 S cm-1 .
[0066] Comparative Example 3
[0067] Weigh 10g of LLZTO and test its alkalinity content to be 3%, and calculate the alkalinity content to be 0.3g. Add 10g of LLZTO powder to 200mL of water, then add 3g of trifluoroacetic acid to neutralize and remove the alkali, and stir for 18h. Then filter to obtain the acid-treated LLZTO, then dry it at 400℃ in a vacuum for 1h to obtain the de-alkali LLZTO, and test its alkalinity content again to be 1.9%. The XRD pattern of the de-alkali LLZTO shows the presence of Li2CO3 impurity phase (such as Fig. 9 ), its lithium ion conductivity is 1.1x10 -4 S cm -1 .
[0068] The test results of the embodiments and comparative examples are shown in Table 1:
[0069] Table 1 Test results of the embodiments of the present invention and comparative examples
[0070]
[0071] It can be seen from the above test results that the method of the present invention has a good alkali removal effect, does not produce impurities, and can inhibit the generation of alkaline substances for a long time.
Claims
1. A method for dealkali treatment of a garnet-type solid electrolyte, characterized in that: The following steps are involved: (1) Testing the alkali content on the surface of garnet-type solid electrolyte; (2) dispersing the garnet-type solid electrolyte in an organic solvent to obtain a garnet-type solid electrolyte dispersion; (3) calculating the mass of the alkali contained in the garnet-type solid electrolyte according to the alkali content obtained in step (1), adding a de-alkali agent to the dispersion of step (2) according to the mass of the alkali, and performing a dispersion treatment, followed by filtering and drying; the de-alkali agent is tetraethylammonium perfluorooctane sulfonate; (4) The alkali content in the garnet-type solid electrolyte was tested again.
2. The dealkali method of garnet-type solid electrolyte according to claim 1, characterized in that: Repeat steps (1)-(4) to further reduce the alkali content of the garnet-type solid electrolyte.
3. The dealkali method of garnet-type solid electrolyte according to claim 1, characterized in that: The alkali content on the surface of the garnet-type solid electrolyte in step (1) includes the mass content of OH- and CO3 2- quality content.
4. The dealkali method of the garnet-type solid electrolyte according to claim 1, characterized in that: The organic solvent described in step (2) is at least one of acetonitrile, ethanol, tetrahydrofuran, carbon disulfide, acetone, N,N-dimethylamide, N,N-dimethylthiourea, melamine, propylene glycol, sorbitol, hydrazine hydrate, dimethyl sulfoxide, N,N-dimethylacetamide, dimethylformamide, acetone, ether, toluene, chloroform, carbon tetrachloride, cyclohexane, petroleum ether, dichloromethane, and ethyl acetate; the mass ratio of the garnet-type solid electrolyte to the volume ratio of the organic solvent is 1g:5~100mL.
5. The dealkali method of garnet-type solid electrolyte according to claim 1, characterized in that: The organic solvent in step (2) is one of ethanol, tetrahydrofuran and carbon disulfide; the mass ratio of the garnet-type solid electrolyte to the volume ratio of the organic solvent is 1 g: 20-50 mL.
6. The dealkali method of the garnet-type solid electrolyte according to claim 1, characterized in that: In step (3), the mass ratio of the alkali to the alkali remover is 1:1-125; and the time of the dispersion treatment is 0.1-30h.
7. The dealkali method of the garnet-type solid electrolyte according to claim 1, characterized in that: The mass ratio of the alkali to the alkali remover in step (3) is 1:10-50.
8. The method for dealkali treatment of a garnet-type solid electrolyte according to claim 1, characterized in that: The time for the dispersion treatment in step (3) is 0.25~18h.
9. The method for dealkali treatment of a garnet-type solid electrolyte according to claim 1, characterized in that: The drying temperature in step (3) is 30-500° C., and the drying time is 1-48 hours.
10. The method for dealkali treatment of a garnet-type solid electrolyte according to claim 1, characterized in that: The drying temperature in step (3) is 100-400° C. and the drying time is 4-24 hours.
Citation Information
Patent Citations
Surface treatment method for garnet type solid electrolyte
CN112290082A
A surface treatment method for garnet-type solid electrolytes
CN112290082B
Composite solid electrolyte and preparation method and application thereof
CN115832412A
Low-residual-alkali long-circulation silicon monoxide carbon material and preparation method thereof
CN116487551A
Composite lithium-rich material and preparation method thereof, positive pole piece and secondary battery
CN117855439A